2018
DOI: 10.7554/elife.38438
|View full text |Cite
|
Sign up to set email alerts
|

Efficient support of virus-like particle assembly by the HIV-1 packaging signal

Abstract: The principal structural component of a retrovirus particle is the Gag protein. Retroviral genomic RNAs contain a ‘packaging signal’ (‘Ψ') and are packaged in virus particles with very high selectivity. However, if no genomic RNA is present, Gag assembles into particles containing cellular mRNA molecules. The mechanism by which genomic RNA is normally selected during virus assembly is not understood. We previously reported (Comas-Garcia et al., 2017) that at physiological ionic strength, recombinant HIV-1 Gag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
(45 reference statements)
3
36
1
Order By: Relevance
“…Thus, the selection of Psi + RNA during virus assembly is evidently not due to a uniquely high affinity of Gag for this RNA. We and others have suggested that binding to Psi induces a nucleating event, such as formation of a small Gag oligomer, more efficiently than binding to other RNAs, and that this difference might underlie the selective packaging of Psi + RNA (7,11,12,(51)(52)(53). The present results provide very strong support for this fundamental concept.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the selection of Psi + RNA during virus assembly is evidently not due to a uniquely high affinity of Gag for this RNA. We and others have suggested that binding to Psi induces a nucleating event, such as formation of a small Gag oligomer, more efficiently than binding to other RNAs, and that this difference might underlie the selective packaging of Psi + RNA (7,11,12,(51)(52)(53). The present results provide very strong support for this fundamental concept.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the selection of Psi + RNA during virus assembly is evidently not due to a uniquely high affinity of Gag for this RNA. We and others have suggested that binding to Psi induces a nucleating event, such as formation of a small Gag oligomer, more efficiently than binding to other RNAs, and that this difference might underlie the selective packaging of Psi + RNA (11,12,(50)(51)(52). The present results provide very strong support for this fundamental concept.…”
Section: Discussionsupporting
confidence: 78%
“…There were also no detected differences from WT protein in the binding of 8N Gag and WM Gag to dimeric Ψ RNA at 300 mM NaCl. We believe that the difference could be caused by the use of shorter RNA constructs and a different measuring buffer; a direct comparison of the fluorescence quenching and microscale thermophoresis binding experiments with a 400 nt long Ψ RNA construct by Comas-Garcia et al [15] found negligible differences between the two experimental techniques. It is also possible that thermophoresis is inherently more sensitive, with regard to weak binding, than the quenching assay.…”
Section: Discussionmentioning
confidence: 98%
“…A previous SHAPE structure-probing analysis of the HIV-1 5 UTR revealed that the main NC interaction domain within Ψ consists of seven short stretches containing unpaired guanosines that are recognized by the NC zinc fingers [13]. It has been shown that mutating these unpaired guanosines interfered with the packaging of the RNA in virus-producing cells [14] and led to the less efficient assembly of the viral particles in vitro [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation